(untitled) (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
This research aims to provide empirical evidence of whether there is an influence of Person-Organization Fit and Personality on Organizational Citizenship Behavior and its impact on Organizational Commitment. This study uses a quantitative correlational method, with data processing assisted by SPSS 22. The population of this study consists of all employees of Hotel Apita Cirebon, including operational and non-operational employees. The sample for this study includes all employees of Hotel Apita Cirebon, totaling 180 individuals. The sample determination uses a saturated sampling method, where the entire population represents the sample of the study. The results of this study indicate that: Person-Organization Fit has a positive effect on Organizational Citizenship Behavior. Personality has a positive effect on Organizational Citizenship Behavior. Person-Organization Fit and Personality together have a positive effect on Organizational Citizenship Behavior. Person-Organization Fit has a positive effect on Organizational Commitment Personality has a positive effect on Organizational Commitment. Organizational Citizenship Behavior has a positive effect on Organizational Commitment. Person-Organization Fit, Personality, and Organizational Citizenship Behavior have a positive effect on Organizational Commitment.